In the city a push and pull adventure - Black, Allison (London ladybird books, 2019)
Explore the busy, bustling city and watch it come to life in this interactive adventure from Little World. Curious minds will love to explore the big city with this interactive title from Little World. Walk the bustling streets and climb towering skyscrapers in this bright and colourful board book, which features a novelty to slide, push or pull on every spread
English stories
Keywords: English stories; Cities and towns Juvenile fiction; Toy and movable books